2005
DOI: 10.3354/meps303123
|View full text |Cite
|
Sign up to set email alerts
|

Seagrass–pathogen interactions: ‘pseudo-induction’ of turtlegrass phenolics near wasting disease lesions

Abstract: Marine protists of the genus Labyrinthula cause the seagrass wasting disease, which is associated with regional die-offs of eelgrass Zostera marina and also infects turtlegrass Thalassia testudinum. The ability of seagrasses to resist pathogen attack is determined by multiple factors, which are poorly understood. One factor hypothesized to influence seagrass disease resistance is the presence of (poly)phenolic natural products such as caffeic acid, which inhibits the growth of L. zosterae in in vitro laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 26 publications
1
44
0
2
Order By: Relevance
“…In addition, trans-cinnamate 4-monooxygenase, an enzyme for phenol synthesis, is upregulated in L. zosteraeinoculated shoots (Brakel et al 2014). However, increased phenolic acid production in turtlegrass T. testudinum is only found in infected leaves above the lesions, not below (Steele et al 2005). Those authors therefore suggest that the production of phenolic acids is not a response to L. zosterae infection, but is a pseudo-induction caused by a disruption in carbohydrate allocation within a leaf leading to higher abundance of carbon above the lesions and thereby an accumulation of phenolic acids.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, trans-cinnamate 4-monooxygenase, an enzyme for phenol synthesis, is upregulated in L. zosteraeinoculated shoots (Brakel et al 2014). However, increased phenolic acid production in turtlegrass T. testudinum is only found in infected leaves above the lesions, not below (Steele et al 2005). Those authors therefore suggest that the production of phenolic acids is not a response to L. zosterae infection, but is a pseudo-induction caused by a disruption in carbohydrate allocation within a leaf leading to higher abundance of carbon above the lesions and thereby an accumulation of phenolic acids.…”
Section: Discussionmentioning
confidence: 78%
“…Steele et al 2005 and references therein). Moreover, some authors have suggested that phenolics may be storage products when organic carbon is present in excess of that which can be metabolised, or as a result of changing patterns of carbon-based resource allocation (Steele et al 2005). However, the only experimentally demonstrated ecological role of specific seagrass phenolics is that of chemical defence against fouling microorganisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Harrison 1982) and with the occurrence of pathogen infection (e.g. Steele et al 2005 and references therein). Moreover, some authors have suggested that phenolics may be storage products when organic carbon is present in excess of that which can be metabolised, or as a result of changing patterns of carbon-based resource allocation (Steele et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These encompassed 41 separate treatments, including re-testing of several isolates. Protocols generally followed those of Renn (1936) and Muehlstein et al (1988), using the same seagrass culture system as Steele et al (2005), and a Bcommon garden^approach to testing the various isolates and hosts. Briefly, plants were collected as single shoots and acclimated for one week as bare-root cultures while submerged singly within 38 L tanks of natural seawater (≈25-30°C and salinity of ≈ 25-30), with a 12:12 h light:dark cycle and a saturating irradiance of 200 μmol PAR m −2 s −1…”
Section: Methodsmentioning
confidence: 99%